Den rumlige vending som ontologisk vending - Ek, Richard (Slagmark - Tidsskrift for idéhistorie, 2018)
For at least twenty years the spatial turn as a concept has been circulating in the Humanities and the Social Sciences, with the result that the meaning of the concept has been more and more known and perhaps even taken for granted in some cases. But as a metaphorical concept, it has its limitations, by necessity. In this article, it is argued that the spatial turn can also be conceptualized as an ontological turn, by a shift of aspect. This argumentation is made through an example, the discussion of one quite recent turn within a specific academic discipline, management and organization theory.